FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA UNIVERSITAS ISLAM INDONESIA YOGYAKARTA DALAM PEMBELIAN HIDANGAN POKOK (PRIMARY DISH) SECARA ONLINE - Rheyza Virgiawan; Luthfiana Kariim (IAIN Batusangkar, 2019)
The research purpose is to increase gratitude for the blessings and gifts of God by means of hifzhnafsh (nurturing the soul) in the analysis of the influence of students’ decision to purchase online primarydishes from Indonesian Islamic University (UII) Yogyakarta. The research was a descriptive qualitativeapproach based on the philosophy of postpositivisme. The sampling used was purposive sampling. Therespondents taken were 64 students of the Indonesian Islamic University (UII) Yogyakarta. Data collectiontechniques were interviews or semi-structured interviews. The results of this study are priority factorsthat influence students’ decision to purchase online primary dishes at the Islamic University of Indonesia(UII) such as halal awareness, likeness, taste, price, health, curiosity, packaging, advertising, lifestyle, andfinally being followers.